HAZARDS BY USING MEL - R. V. Enikeev (Научный вестник МГТУ ГА)
The article covers the problem of understanding of hazard identification necessity by using Minimum Equipment List (MEL) in civil aviation of the Russian Federation. The examples of hazards by using MEL are given in the article. It is also pointed out the seriousness of the consequences associated with the hazards and necessity of subsequent risk assessment.